Time course of cytochrome oxidase blob plasticity in the primary visual cortex of adult monkeys after retinal laser lesions - Farias, Mariana F. (J Comp Neurol, 2018)
We studied the time course of changes of cytochrome oxidase (CytOx) blob spatial density and blob cross-sectional area of deprived and non-deprived portions of V1 in four capuchin monkeys after massive and restricted retinal laser lesions. Laser shots at the border of the optic disc produced massive retinal lesions, while low power laser shots in the retina produced restricted retinal lesions. These massive and restricted retinal lesions were intended to stimulate glaucoma and diabetic retinopathy, respectively. We used a Neodymium -YAG dual frequency laser to make the lesions. We measured layer III blobs in CytOx-reacted tangential sections of flat-mounted preparations of V1. The plasticity of the blob system and that of the ocular dominance columns (ODC) varied with the degree of retinal lesions. We found that changes in the blob system were different from that of the ODC. Blob sizes changed drastically in the region corresponding to the retinal lesion. Blobs were larger and subjectively darker above and below the non-deprived ODC than in the deprived columns. With restricted lesions, blobs corresponding to the non-deprived columns had sizes similar to those from non-lesioned areas. In contrast, blobs corresponding to the deprived columns were smaller than those from non-lesioned areas. With massive lesions, non-deprived blobs were larger than the deprived blobs. Plastic changes in blobs described here occur much earlier than previously described.